2016
DOI: 10.1080/19440049.2016.1143566
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of enrofloxacin residues in broiler tissues using ELISA and LC-MS/MS

Abstract: This study investigated the efficiency of an enrofloxacin ELISA test kit to detect the presence of enrofloxacin residues in broiler tissues compared with LC-MS/MS. Broiler tissues from 72 samples consisting of 60 breast muscle, six pools of livers (500 g each) and six pools of kidneys (500 g each) were obtained from six different slaughterhouses. Breast muscle from 10 carcasses and pools of livers and kidneys from approximately 200 carcasses of the same flock were collected from each slaughterhouse. ELISA and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 19 publications
3
13
1
Order By: Relevance
“…The detection of ENR in edible tissues of broilers have also been evaluated in those reports (de Assis et al, 2016; Haag et al, 2016; Panzenhagen et al, 2016). Establishment of withdrawal periods are based on the depletion times of drugs, which allows the appropriate animal treatment and slaughter of treated animals, according to the requirement for the elimination and residues of drugs in animal tissues.…”
Section: Introductionmentioning
confidence: 99%
“…The detection of ENR in edible tissues of broilers have also been evaluated in those reports (de Assis et al, 2016; Haag et al, 2016; Panzenhagen et al, 2016). Establishment of withdrawal periods are based on the depletion times of drugs, which allows the appropriate animal treatment and slaughter of treated animals, according to the requirement for the elimination and residues of drugs in animal tissues.…”
Section: Introductionmentioning
confidence: 99%
“…The highest levels of resistance were observed in abattoir 3 (Table 2), a commercial abattoir, located at metropolitan region of Rio de Janeiro In Brazil, enrofloxacin is frequently employed in poultry breeding, and there is no effective control by regulatory agencies of its use in small producers, as may be verified in the report of the State Program for the Control of Veterinary Medicine Wastes in Animal-derived Food (PAMvet) in the state of Paraná, Brazil (Machinski Junior et al 2005). In fact, Panzenhagen et al (2016b) registered enrofloxacin wastes in 72.2% of broilers' samples collected in the state of Rio de Janeiro, analyzed by Enzyme-Linked Immunosorbent Assay (ELISA), albeit at rates lower than the Maximum Waste Limits. In Spain, Cantero et al (2018) reported that (Lin et al 2002) isolated strains of broilers were predominantly resistant to quinolones, perhaps due to the frequent use of enrofloxacin in poultry breeding.…”
Section: Resultsmentioning
confidence: 99%
“…Quinolones are powerful options among the antimicrobial agents employed in the treatment of various bacterial-caused poultry diseases (29). In addition, the presence of quinolones in poultry products causes public health concerns (21). Local and international regulatory and public health agencies give attention to screening of antibiotic residues in foodproducing animals.…”
Section: Discussionmentioning
confidence: 99%
“…Fluoroquinolones, essential drugs for human and animal health, are widely used for the treatment of several diseases in veterinary medicine (21,24). Enrofloxacin (ENR), a common fluoroquinolone, has a broad spectrum of action and exhibits high efficacy against infectious diseases that are caused by mycoplasma and gram-positive and gram-negative bacteria (14,21).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation